Dosagem da amilosúria em bovinos parasitados pelo eurithrema coelomaticum - Côdo, Vitório (Revista Ceres, 1953)
In attempting to find a method of diagnosis with which to dose the pancreatic amylase eliminated by bovins in the urine, the author used the technique of Wohlgermuth, in order to ascertain if the amylase determined physiologically, would suffer any change, in case the organs were parasitized by, Eurithrema coelomaticum, trematode of the pancreas of bovins. The amylase eliminated by the urine was dosed in 65 heads of cattle at the slaughter house. By this method it was not possible to explain the diagnosis of the infestation by the E. coelomaticum. In order to obtain the material to be examined, were used only animals at the slaughter house.